Distribution and metabolism of iPSC-MSCs in the joint cavity of an osteoarthritis rat model - Yuan, Xiaoyang; Wang, Xulei; Du, Tianxi; Zhang, Feng; Cheng, Gang; Wang, Kang; Xu, Haochen; Yang, Pingting; Chang, Yan; Wei, Wei; He, Peng; Yan, Shangxue (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionTo investigate the metabolism and distribution of iPSC‐MSCs in the joint cavity of rats with knee osteoarthritis (KOA).MethodsThe iPSC‐MSCs labeled with the Antares2 luciferase gene were injected into the knee joints of rats, and then the metabolism and distribution of the cells in vivo were revealed by imaging and molecular biomarker methods.ResultHistopathological results demonstrated that iPSC‐MSCs significantly reversed joint tissue damage of arthritic rats. The fluorescence signal of iPSC‐MSCs labeled with Antares2 luciferase gene was stable and persistent with high detection sensitivity. The fluorescent signal duration of Antares2‐iMSCs in the joint cavity of KOA rats was approximately 2 weeks, which was significantly longer than 1 week in the sham‐operated group. The proportion of iPSC‐MSCs in the synovial fluid gradually decreased over time, and for the first time, the cells were observed to attach to the synovium first, followed by the meniscus and cartilage.DiscussionThis study was the first to explore the metabolism and distribution of iPSC‐MSCs after intra‐articular injection by labeling the Antares2 luciferase gene, which provides assurance and theoretical basis for the safety of clinical application of iPSC‐MSCs in treating osteoarthritis.